Pola Pengambilan Putusan Perencanaan Karier Siswa Berbakat Intelektual - Tuti, Meiri Dias; Tjahjono, Evy; Kartika, Aniva (ANIMA Indonesian Psychological Journal, 2006)
Intellectually gifted students face problems in career planning due to their varied interests and potentials. This explorative study aimed to describe the pattern of career planning decision making in intellectually gifted students. The informant is an intellectually gifted student, a participant of an acceleration program in ”X” Senior Highschool in Surabaya. Data were collected by using semi structured interviews, depth interviews and documentations. The results indicate that an intellectually gifted student who has limited career information in her childhood and adolescence periods may begin her career planning during her Senior Highschool period when information has been provided. Interests, aptitudes, abilities, information about working environments, diseases, and parental supports are some considerations that should be taken in making the decision. Significant figures supporting the decision making are parents, psychologists, and teachers. Siswa berbakat intelektual seringkali mengalami masalah perencanaan karier karena memiliki minat dan potensi beragam. Penelitian eksploratif ini bertujuan menggambarkan pola pengambilan putusan perencanaan karier. Informan adalah satu siswa berbakat intelektual peserta program percepatan belajar di SMA ”X” Surabaya. Data dikumpulkan melalui wawancara semi terstruktur, wawancara mendalam serta dokumentasi. Hasil menunjukkan siswa berbakat intelektual dengan keterbatasan informasi karier pada masa kanak-kanak dan remaja awal baru merencanakan karier pada masa SMA ketika informasi karier tersedia. Faktor minat, bakat, kemampuan, informasi lingkungan kerja, prospek kerja, penyakit, dan dukungan orang tua merupakan pertimbangan dasar dalam pengambilan putusan. Figur penting yang membantu pengambilan putusan perencanaan karier adalah orang tua, psikolog, dan guru.